Source-Sink Dynamics in Field-Grown Durum Wheat Under Contrasting Nitrogen Supplies: Key Role of Non-Foliar Organs During Grain Filling - Martínez-Peña, Raquel; Schlereth, Armin; Höhne, Melanie; Encke, Beatrice; Morcuende, Rosa; Nieto-Taladriz, María Teresa; Araus, José Luis; Aparicio, Nieves; Vicente, Rubén (Frontiers in Plant Science, 2022)
The integration of high-throughput phenotyping and metabolic approaches is a suitable strategy to study the genotype-by-environment interaction and identify novel traits for crop improvement from canopy to organ level. Our aims were to study the phenotypic and metabolic traits that are related to grain yield and quality at canopy and organ level, with a special focus on source-sink coordination under contrasting N supplies. Four modern durum wheat varieties with contrasting grain yield were grown in field conditions under two N fertilisation levels in north-eastern Spain. We evaluated canopy vegetation indices taken throughout the growing season, physiological and metabolic traits in different photosynthetic organs (flag leaf blade, sheath, peduncle, awn, glume and lemma) at anthesis and mid grain filling stages, and agronomic and grain quality traits at harvest. Low N supply triggered an imbalance of C and N coordination at the whole plant level, leading to a reduction of grain yield and nutrient composition. The activities of key enzymes in C and N metabolism as well as the levels of photoassimilates showed that each organ plays an important role during grain filling, some with a higher photosynthetic capacity, others for nutrient storage for later stages of grain filling, or N assimilation and recycling. Interestingly, the enzyme activities and sucrose content of the ear organs were positively associated with grain yield and quality suggesting, together with the regression models using isotope signatures, the potential contribution of these organs during grain filling. This study highlights the use of holistic approaches for the identification of novel targets to improve grain yield and quality in C3 cereals and the key role of non-foliar organs at late growth stages.